Disease Control Priorities, Third Edition : Volume 4. Mental, Neurological, and Substance Use Disorders - Patel, Vikram; Chisholm, Dan; Dua, Tarun; Laxminarayan, Ramanan; Medina-Mora, Maria Elena (Washington, DC: World Bank, 2016)
Mental, neurological, and substance use disorders are common, highly disabling, and associated with significant premature mortality. The impact of these disorders on the social and economic well-being of individuals, families, and societies is large, growing, and underestimated. Despite this burden, these disorders have been systematically neglected, particularly in low- and middle-income countries, with pitifully small contributions to scaling up cost-effective prevention and treatment strategies. Systematically compiling the substantial existing knowledge to address this inequity is the central goal of this volume. This evidence-base can help policy makers in resource-constrained settings as they prioritize programs and interventions to address these disorders.